2017
DOI: 10.1074/jbc.m117.799346
|View full text |Cite
|
Sign up to set email alerts
|

The Alzheimer's disease–protective CD33 splice variant mediates adaptive loss of function via diversion to an intracellular pool

Abstract: The immunomodulatory receptor Siglec-3/CD33 influences risk for late-onset Alzheimer's disease (LOAD), an apparently human-specific post-reproductive disease. generates two splice variants: a full-length CD33M transcript produced primarily by the "LOAD-risk" allele and a shorter CD33m isoform lacking the sialic acid-binding domain produced primarily from the "LOAD-protective" allele. An SNP that modulates CD33 splicing to favor CD33m is associated with enhanced microglial activity. Individuals expressing more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 69 publications
6
72
2
Order By: Relevance
“…AD and PD genome-wide association studies (GWASs) and more recent meta-analyses of these GWASs implicate a number of loci that contain immune genes in mediating risk (Chang et al, 2017; Hamza et al, 2010; Hill-Burns et al, 2011; International Geno-mics of Alzheimer's Disease Consortium (IGAP), 2015; Lambert et al, 2010;Lambert et al, 2009;Nalls et al, 2014;Reitz et al, 2013;Wissemann et al, 2013;Witoelar et al, 2017). Unfortunately, there remains limited biological insight into how variants at these loci alter immune function, though some clues are emerging (Bradshaw et al, 2013;Brouwers et al, 2012;Carrasquillo et al, 2017;Huang et al, 2017;Katsumata et al, 2019;Siddiqui et al, 2017). Indeed, in many cases, though an immune gene is embedded within the region implicated by the GWASs, the locus implicated is typically larger than a single gene and may contain both genes with known or purported immune function and genes with other functions.…”
Section: Can We Resolve This Dilemma?mentioning
confidence: 99%
“…AD and PD genome-wide association studies (GWASs) and more recent meta-analyses of these GWASs implicate a number of loci that contain immune genes in mediating risk (Chang et al, 2017; Hamza et al, 2010; Hill-Burns et al, 2011; International Geno-mics of Alzheimer's Disease Consortium (IGAP), 2015; Lambert et al, 2010;Lambert et al, 2009;Nalls et al, 2014;Reitz et al, 2013;Wissemann et al, 2013;Witoelar et al, 2017). Unfortunately, there remains limited biological insight into how variants at these loci alter immune function, though some clues are emerging (Bradshaw et al, 2013;Brouwers et al, 2012;Carrasquillo et al, 2017;Huang et al, 2017;Katsumata et al, 2019;Siddiqui et al, 2017). Indeed, in many cases, though an immune gene is embedded within the region implicated by the GWASs, the locus implicated is typically larger than a single gene and may contain both genes with known or purported immune function and genes with other functions.…”
Section: Can We Resolve This Dilemma?mentioning
confidence: 99%
“…caused by a translocation of intracellular pool to the cell surface (Siddiqui et al 2017). It has been reported that the stimulation of LPS results in increased surface expression of CD11b, and CD35 on monocytes, suggesting that these rapid changes may be caused by the inflammatory response (Furebring et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…CD33 has a high expression on monocyte surface as well as in an internal compartment after stimulation of formylated peptides (fMLP), a bacterial-derived peptide. This could affect the expression of CD33 on the cell surface in response to an inflammatory stimulus (Siddiqui et al 2017). It is also found that the high antigen induction on the cell surface upon E. coli activation may imply the preformed intracellular pool of surface antigen which was rapidly translocated to the surface upon activation of these cells (Siddiqui et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell stimulation and activation did not mobilize D2-CD33 to the surface. Thus, the D2-CD33 isoform may neither interact directly with amyloid plaques nor engage in cell surface signaling, demonstrating a loss of function mechanism [20]. Moreover, CD33 may interact with other microglial AD risk genes to influence AD onset and pathogenesis.…”
Section: Cd33 and Ad Pathologiesmentioning
confidence: 99%